An in-Situ Impedance-Based Whole Blood Anticoagulation Diagnosis Technology. (9th April 2019) - Huang, Yi-Chen; Chiang, Kuang-Hsing; Jheng, Jhu-Siang; Lin, Chih-Ting
Abstract : The detection of anticoagulant dosage in blood is important and necessary in clinical operations. With high anticoagulant dosage, it results in heavy bleeding during surgery. With low anticoagulant dosage, in the opposite, it leads to clotting problem. To monitor the dosage, in traditional, optical-inspection instrumentations, such as PT (Prothrombin Time) and APTT (Activated Partial Thromboplastin Time), are commonly used in hospitals. However, the processes of PT and APTT measurements are complicated and time-consuming. To address these issues, in this work, electrical impedance analysis is employed to monitor the anticoagulant dosage in the whole blood samples obtained from rats. To optimize the impedance analysis, several electrode designs are implemented and examined. According to the experimental results, the more heparin adds, the larger slope value from the linear regression analysis can be extracted, and a good electrode configuration for blood coagulation measurement is tested with whole blood extracted from rats.